JBI series paper 2: tailored evidence synthesis approaches are required to answer diverse questions: a pragmatic evidence synthesis toolkit from JBI - Aromataris, Edoardo; Stern, Cindy; Lockwood, Craig; Barker, Timothy H; Klugar, Miloslav; Jadotte, Yuri; Evans, Catrin; Ross-White, Amanda; Lizarondo, Lucylynn; Stephenson, Matthew; McArthur, Alexa; Jordan, Zoe; et al. (Journal of clinical epidemiology, 2022)
Evidence synthesis is critical in evidence-based healthcare and is a core program of JBI. JBI evidence synthesis is characterised by a pluralistic view of what constitutes evidence and is underpinned by a pragmatic ethos to facilitate the use of evidence to inform practice and policy. This second paper in this series provides a descriptive overview of the JBI evidence synthesis toolkit with reference to resources for 11 different types of reviews. Unique methodologies such as qualitative syntheses, mixed methods reviews, and scoping reviews are highlighted. Key features include standardised and collaborative processes for development of methodologies and a broad range of tailored resources to facilitate the conduct of a JBI evidence synthesis, including appraisal and data extraction tools, software to support the conduct of a systematic review and an intensive systematic review training program. JBI is one of the leading international protagonists for evidence synthesis, providing those who want to answer health-related questions with a toolkit of resources to synthesize the evidence.
Keywords: lékařská praxe založená na důkazech; Software; Policy; software; lidé; postup; Evidence-Based Practice; Humans